Austin Donnelly interviewed by John Farquharson - Donnelly, Austin, 1923-2007.; Farquharson, John M., 1929-2016 (2001)
Austin Donnelly, semi-retired investment adviser & author, discusses the growth of the financial advising industry, the importance of communication in business and the responsibilities of directors. He recalls the background to how he came to write his books. Donnelly talks about market cycles; the questionable loan activities of the banks in the 1980s; business collapses; role of the Australian Investors' Association in educating and giving an effective voice to the investing public and the impact of the GST. He speaks about his role as an expert witness in court cases concerning business matters; gives some recollections of Sir Arthur Fadden (Treasurer in the Menzies Government), the economic outlook in the wake of the Sept. 11 (2001) terrorist attacks in the United States and the gender state of the financial advising business.
Recorded on Sept. 26, 2001 at Canberra, A.C.T.
Digital master available
This interview with Austin Donnelly, financial & investment adviser, is an update on an earlier interview conducted by Hazel De Berg in March 1975. At that time Donnelly, one of Australia's earliest financial advisers- he holds Licence No. 1-had written 21 textbooks on investment, finance and aspects of business management. Now his output of such books has reached 50. His personal background and early work as an accountant before branching out into the financial and investment advising field is covered in the Hazel De Berg interview.
Timed summary (2 p.) and completed transcript (typescript, 45 leaves)
Keywords: Donnelly, Austin, -- 1923-2007 -- Interviews; Investment advisors -- Australia -- Interviews; Authors, Australian -- Interviews; Investment analysis -- Australia; Banks and banking -- Australia; Wealth -- Economic aspects -- Australia; Investment advisors; Authors